2019
DOI: 10.3808/jeil.201900002
|View full text |Cite
|
Sign up to set email alerts
|

Flood-Drought Hazard Assessment for a Flat Clayey Deposit in the Canadian Prairies

Abstract: Dry climate, clayey soil, and flat topography govern water balance in the southern part of the Canadian Praries. This paper aims at assessing flood-drought hazard using Regina as a typical urban centre in the region. The main achievements are the inclusion of long-term historical analyses of recent meteorological data, physiographic features (such as topography, land use, soil type) of watersheds, various types of drought (agricultural, metrological, and hydrological), and management strategies for surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Among the results of the last 5 years the Chinese scientists research on the effects of solar activity on floods and droughts (Li et al, 2015), an assessment of the effects of climate change on hydrological extremes -floods and droughts within the territory of Poland (Romanowicz, 2017); a thorough corporate study by European scientists on the effects of climate change on the water resources of Europe's largest water artery -the Danube Basin (Bisselink et al, 2018) should be noted. Similar researches are done about the rivers of Algeria (Kouidri et al, 2019) and the Canadian Prairies (Akhter and Azam, 2019). In Ukraine, the research of the water regime of rivers and its changes nowa-days is actively done by the scientists of Taras Shevchenko National University and their colleagues from the Potsdam Institute for Climate Impact Study (Lobanova et al, 2018), representatives of the Ukrainian Hydrometeorological Institute (Zabolotnia et al, 2019) and Odessa State Environmental University (Loboda et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…Among the results of the last 5 years the Chinese scientists research on the effects of solar activity on floods and droughts (Li et al, 2015), an assessment of the effects of climate change on hydrological extremes -floods and droughts within the territory of Poland (Romanowicz, 2017); a thorough corporate study by European scientists on the effects of climate change on the water resources of Europe's largest water artery -the Danube Basin (Bisselink et al, 2018) should be noted. Similar researches are done about the rivers of Algeria (Kouidri et al, 2019) and the Canadian Prairies (Akhter and Azam, 2019). In Ukraine, the research of the water regime of rivers and its changes nowa-days is actively done by the scientists of Taras Shevchenko National University and their colleagues from the Potsdam Institute for Climate Impact Study (Lobanova et al, 2018), representatives of the Ukrainian Hydrometeorological Institute (Zabolotnia et al, 2019) and Odessa State Environmental University (Loboda et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…Likewise, Figure 3b shows that the daily air temperature is above 0 ℃ for 350, 210, and 143 days for the above conditions. The high number of days with above 0 ℃ temperature correlates well with the semi-arid regional climate (Akhter and Azam, 2019;Shook and Pomeroy, 2016). Using the Köppen-Geiger climate classification system (Kottek et al, 2006), the atmospheric parameters for dry and mean conditions were found to be cold desert climate (BWk) whereas the wet condition was classified as cold arctic climate (Dfc).…”
Section: Atmospheric Parametersmentioning
confidence: 95%
“…Cyclic precipitation-evaporation during spring-summer-fall as well as freeze-thaw during the fall-winter-spring result in ground deformation and slope instability. Furthermore, extreme weather events such as flash-floods and long-droughts have been observed throughout the region and are attributed to the adverse effects of climate change (Bonsal et al, 2017;Akhter and Azam, 2019). Such uncertainties of seasonal weather impose serious concerns on the efficiency of buried utilities (Kleiner and Rajani, 2002;Yang and Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the Penman evaporation method is critical to understanding the relationship between climate change and drought indices [2]. The region is prone to frequent and severe droughts [3] and climate change could exacerbate this situation. A report by the Saskatchewan Ministry of Agriculture recommends a 400% increase in irrigated area to address serious issues with respect to food security and economic development [4].…”
Section: Introductionmentioning
confidence: 99%